Strongly structured populations and reproductive habitat fragmentation increase the vulnerability of the Mediterranean starry ray Raja asterias (Elasmobranchii, Rajidae). Issue 1 (19th November 2021) - Catalano, Giusy; Crobe, Valentina; Ferrari, Alice; Baino, Romano; Massi, Daniela; Titone, Antonino; Mancusi, Cecilia; Serena, Fabrizio; Cannas, Rita; Carugati, Laura; Hemida, Farid; Manfredi, Chiara; et al.
Abstract: The Mediterranean starry ray ( Raja asterias ) populations within the Mediterranean Sea are susceptible to high rates of bycatch in the multispecies trawl fisheries. Understanding its population structure and identifying critical habitats are crucial for assessing species vulnerability and setting the groundwork for specific management measures to prevent population decline. To assess the population structure of R. asterias in the Mediterranean, the genetic variation in nine population samples at one mitochondrial marker and eight nuclear microsatellite loci was analysed. Moreover, 172 egg cases collected in the Strait of Sicily were identified at species level using integrated molecular and morphological approaches. Genetic analyses revealed that the Mediterranean starry ray comprises three distinct units inhabiting the western, the central‐western, and the central‐eastern areas of the Mediterranean. An admixture zone occurs in the Strait of Sicily and the Ionian Sea, where individuals of the central‐western and central‐eastern population units intermingle. The joint morphometric–genetic analyses of rajid egg cases confirmed the presence of more than one species in the admixture area, with a predominance of egg cases laid by R. asterias . DNA barcoding revealed that egg cases and embryos of R. asterias shared several haplotypes with adult individuals from the central‐western and central‐eastern Mediterranean Sea, revealing that females of both populations laid numerous eggs in this area. According to these findings, detailed taxonomic determination of egg cases, when combined with seasonal migration studies, could improve the capability to identify important spawning or nursery areas for the Mediterranean starry ray, particularly in those admixture zones relevant to maintaining genetic diversity. Finally, these new insights should be considered to update the Action Plan for the Conservation of Cartilaginous Fishes in the Mediterranean Sea with effective measures to reduce the impact of skate bycatch in trawling and safeguard egg cases in nursery areas.